PERTUMBUHAN KELOMPOK SEL DITINJAU DARI KESATUAN HATI, TUMBUH BERSAMA DAN MEMENANGKAN JIWA - Eko Agus Setiawan (JURNAL IMPARTA, 2022)
One of the eight characteristics of a healthy church according to Christian Schwarz is empowering the congregation in small groups. A church that has a large number of congregations when it is not accompanied by the formation of cell groups will stagnate or experience a decline in the dynamics of church service to its congregations. Some churches are starting to realize how important cell groups are for church service to their congregations because cell groups are an extension of the pastor's hand so that they build interaction between one congregation and another. The growth of the cell group is influenced by 3 variables, namely the unity of the heart, the commitment to grow together and the desire to win souls. From the results of research conducted on 176 congregations who have joined the cell group, it can be seen that the variables of heart unity, growing together and winning souls have an effect of 76.8% on the growth of cell groups.